Sexual reproduction in land plants: an evolutionary perspective - Annette Becker; Xia Chen; Thomas Dresselhaus; Nora Gutsche; Stefanie J. Müller-Schüssele; Stefanie Sprunck; Günter Theißen; Sophie de Vries; Sabine Zachgo (Plant Reproduction, 2025)
Key message We link key aspects of land plant reproductive evolution and detail how successive molecular changes leading to novel tissues and organs require co-evolution of communication systems between tissues. Abstract The transition of water-dependent reproduction of algae to mechanisms with very limited water dependence in many land plant lineages allowed plants to colonize diverse terrestrial environments, leading to the vast variety of extant plant species. The emergence of modified cell types, novel tissues, and organs enabled this transition; their origin is associated with the co-evolution of novel or adapted molecular communication systems and gene regulatory networks. In the light of an increasing number of genome sequences in combination with the establishment of novel genetic model organisms from diverse green plant lineages, our knowledge and understanding about the origin and evolution of individual traits that arose in a concerted way increases steadily. For example, novel members of gene families in signaling pathways emerged for communication between gametes and gametophytes with additional tissues surrounding the gametes. Here, we provide a comprehensive overview on the origin and evolution of reproductive novelties such as pollen grains, immobile sperms, ovules and seeds, carpels, gamete/gametophytic communication systems, double fertilization, and the molecular mechanisms that have arisen anew or have been co-opted during evolution, including but not limited to the incorporation of phytohormones, reactive oxygen species and redox signaling as well as small RNAs in regulatory modules that contributed to the evolution of land plant sexual reproduction.